Erythrocyte G-6PD levels in puerperium - Hiçsönmez, Gönül; Özsoylu, Şinasi (The Turkish Journal of Pediatrics, 1969)
Erythrocyte G-6PD activity was assayed in 30 mothers, who did not have anemia, within three to seven days of parturition, and was compared to control female values. This enzyme was found statistically higher in the mothers than in the controls.